2006
DOI: 10.1529/biophysj.105.069393
|View full text |Cite
|
Sign up to set email alerts
|

Transition in the Temperature-Dependence of GFP Fluorescence: From Proton Wires to Proton Exit

Abstract: In green fluorescent protein, photo-excitation leads to excited-state proton transfer from its chromophore, leaving behind a strongly fluorescing anion, while the proton is commonly thought to migrate internally to Glu-222. X-ray data show that the protein contains more extended hydrogen-bonded networks that can support proton migration (i.e., proton wires). Here we study the temperature-dependence of the transient fluorescence from both the acid and anionic forms up to 15 ns. At low temperatures, we find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
105
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(115 citation statements)
references
References 37 publications
10
105
0
Order By: Relevance
“…40 Nevertheless, time-resolved fluorescence data from GFP suggested that this proton might exhibit much richer dynamics, which includes drunkard motion along a wire with possible escape to solution. 43,46 The present MD investigation shows that the PWM exhibits equally rich dynamics.…”
Section: Resultsmentioning
confidence: 58%
“…40 Nevertheless, time-resolved fluorescence data from GFP suggested that this proton might exhibit much richer dynamics, which includes drunkard motion along a wire with possible escape to solution. 43,46 The present MD investigation shows that the PWM exhibits equally rich dynamics.…”
Section: Resultsmentioning
confidence: 58%
“…48 This constitutes the aromatic chromophore, whose anion fluoresces in the green following an excited state PT reaction. 26,28 Cyclization occurs only after protein folding, within a tight R-helical turn that places the Gly67 amide in close proximity to the Ser65 carbonyl, resulting in nucleophilic attack and ring formation (Scheme 2). Tsien and co-workers suggested that chromophore biosynthesis in GFP consists of three steps: cyclization, dehydration, and oxidation (see Scheme 3).…”
Section: Chromophore Biosynthesis In Gfpmentioning
confidence: 99%
“…Reversible recombination, which is coupled to onedimensional diffusion along the wire, occasionally regenerates the acidic (Tyr66-OH) form, resulting in a t -1/2 long-time tail in its time-resolved fluorescence signal. 28,29 The side chain of Thr203 may subsequently rotate, establishing a short pathway for proton exit into solution. 22,29 GFP is a very rigid protein, 30 so it may not be surprising if most of its proton wires are observed already in its static X-ray structure.…”
Section: Introductionmentioning
confidence: 99%
“…One way to rationalize this result is that the short hydrogen bond leads to a more delocalized proton, that is, there is only one potential well involved. Thus, after excitation only a small proton displacement is required to generate a green-emitting state, and this process in the excited state of A β is barely dependent upon the hydrogen isotope or temperature on the ultrafast timescale that we can detect.Previous spectroscopic and structural studies on wild-type GFP suggest that excitation of the neutral chromophore at 400 nm leads to excited-state proton transfer from the chromophore to a proton acceptor on the tens of ps timescale, possibly through a hydrogen-bonding network, and this excited-state interconversion process can be slowed down significantly by deuterating exchangeable protons or cooling (2,(6)(7)(8)(10)(11)(12)24). Recent studies on dual-emission GFPs are consistent with this overall scheme, though the rates of proton transfer and non-radiative processes and the identity of the proton acceptor and transfer pathway(s) may be different (13-15).…”
mentioning
confidence: 99%